Noise Control (IntechOpen, 2023)
This book describes advances in the field of noise control. It includes six chapters that discuss different control techniques, EVAC systems, the effects of the pandemic on environmental noise, and more. Chapters present different situations and case studies to better elucidate noise control approaches and applications, including noise mapping and outdoor barriers.